2014
DOI: 10.1164/rccm.201406-1167le
|View full text |Cite
|
Sign up to set email alerts
|

Airway Basal Stem/Progenitor Cells Have Diminished Capacity to Regenerate Airway Epithelium in Chronic Obstructive Pulmonary Disease

Abstract: Cigarette smoking, and the eventual development of chronic obstructive pulmonary disease (COPD) in susceptible individuals, is characterized by disordered differentiation of the small airway epithelium (SAE) (1, 2). The SAE is composed of four major cell types, the differentiated ciliated and secretory cells responsible for lung defense and the undifferentiated intermediate and basal cells that function as the stem/progenitor cells of the ciliated and secretory cells (3,4). On the basis of the knowledge that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 17 publications
1
87
1
1
Order By: Relevance
“…The advantage of this option is underlined by the observation that ALI-cultured airway epithelial cells derived from patients with mild or severe asthma retain characteristics of the distorted airway epithelium present in the patients lungs, and that the phenotypic differences relate to the severity of asthma (Gras et al, 2012). Similar observations have been reported in COPD (Amatngalim et al, 2017;Staudt et al, 2014), suggesting that the lung microenvironment in these inflammatory lung diseases causes (epigenetic) changes in epithelial cells resulting in partial persistence of the phenotype in culture.…”
Section: Primary Lung Epithelial Cellsmentioning
confidence: 66%
“…The advantage of this option is underlined by the observation that ALI-cultured airway epithelial cells derived from patients with mild or severe asthma retain characteristics of the distorted airway epithelium present in the patients lungs, and that the phenotypic differences relate to the severity of asthma (Gras et al, 2012). Similar observations have been reported in COPD (Amatngalim et al, 2017;Staudt et al, 2014), suggesting that the lung microenvironment in these inflammatory lung diseases causes (epigenetic) changes in epithelial cells resulting in partial persistence of the phenotype in culture.…”
Section: Primary Lung Epithelial Cellsmentioning
confidence: 66%
“…Stem cell niches fail to respond effectively to additional demands for cell turnover; moreover, deranged metabolic signalling and premature senescence might occur [141]. In line with this, reduced regenerative capacity of basal progenitor cells has been reported in COPD [135]. In addition, in a different study, an abnormal population of TRP63 + KRT5 + KRT14 + basal cells was identified in regions of hyperplasia from sections of COPD human airways [142], suggesting abnormal stem cell function.…”
Section: Stem Cell Exhaustionmentioning
confidence: 71%
“…Airway basal cells represent a well-characterised stem cell population located in the trachea and bronchi. These cells have the ability to self-renew and give rise to secretory, ciliated and neuroendocrine cells [135]. In the distal lung, alveolar type II cells [136] have been shown to be able to replenish lost alveolar type II cells and transdifferentiate to alveolar type I cells, thus ensuring proper gas exchange [132,133].…”
Section: Stem Cell Exhaustionmentioning
confidence: 99%
“…Staudt and colleagues (62) demonstrated that when basal cells obtained from the small airway epithelium are placed on air-liquid interface and allowed to differentiate to a mucociliated epithelium over 28 days, 88% of samples isolated from healthy nonsmokers successfully regenerated airway epithelium, but only 64% of those from normal smokers and only 44% of those from smokers with COPD regenerated. Inability to form mechanically stable and properly differentiated airway epithelium by basal cells of smokers with COPD may underlie decreased host defense function and barrier integrity of the airway epithelium in patients with COPD, potentially leading to infection and inflammation, which contribute to progression of COPD as chronic disease.…”
Section: Smoking To Copdmentioning
confidence: 99%